Analysis of Neutron Radiation Absorption Capacity of Coir Fiber Composite Board as A Neutron Radiation Shield - Sitepu, Evi Christiani; Simatupang, Dimas Frananta (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2025)
Research has been conducted on the radiation shielding capability of coir fiber composite boards to determine the extent of neutron radiation absorption as it passes through the created radiation shield. This study aims to ascertain whether coir fiber can be used as a filler in the production of radiation shields. Initial analysis was conducted using SEM-EDX, FTIR, and XRD testing. The results indicated that the primary component of coir fiber is carbon at 70.68%, which is structured in chemical bonds of cellulose, hemicellulose, and lignin. Additionally, coir fiber retains a crystalline region observed at the peak of 2θ=22.4°, with a crystallinity degree of 35.46%, suggesting its potential for neutron radiation absorption. After fabricating the composite board, it was tested using the Neutron Activation Analysis method to evaluate its neutron radiation absorption capability. The analysis results showed that the absorption capacity of the composite board at a fiber mass fraction of 2.0 g ranged from 59.4 to 97.8%; at 3.0 g from 64.3 to 98.3%; and at 4.0 g from 73.5 to 99.3%. The linear attenuation coefficients (µ) for each coir fiber fraction were found to be 3.84; 4.13; and 4.80/cm, with half-value layers of 0.18; 0.17; and 0.14 cm, respectively, demonstrating that coir fiber can be utilized as a filler for neutron radiation shielding.